Application of Multimedia Digital Story Telling in Speaking Learning at Information Technology Study Program - Lela Rahmawati; Hilda Hastuti; Wahyu Kamil Syarifaturrahman; Agus Syahid; Puspita Dewi (Humanitatis : Journal of Language and Literature, 2023)
This article explains how project-based learning is being implemented (digital storytelling) to help students in the First Semester in Bumigora University in Mataram at become more proficient speakers. The aims of this research are to find out whether Project-Based Learning (digital storytelling) can improve students’ speaking skill and to analyze the students’ learning motivation when is implemented. A test, questionnaire, interview, and observation were used to gather the data. The researchers used action research and random sampling technique. The method used mix method, quantitative and qualitative. The steps in this design are Planning, acting, observing, and reflecting. The study's conclusions showed that students' speaking abilities had improved in a number of areas, including confidence, fluency, pronunciation, grammar, and vocabulary. A range of speaking exercises, such as oral presentations, voice recordings, group discussions, and interviews, helped to strengthen those areas. The study's conclusions showed that pupils' speaking abilities had improved in a number of areas, including confidence, fluency, pronunciation, grammar, and vocabulary. A range of speaking exercises, such as oral presentations, voice recordings, group discussions, and interviews, helped to strengthen those areas. Moreover, the mean gain of the students’ post-test was higher than the mean gain of the students’ pre-test. In the pre-test, the mean gain was 56.37; however, the students could achieve 74.05 in the post-test. In addition, students’ learning motivation increased in terms of: students involve in learning process, students solve the problem and search the issue, students try to work harder to avoid the failure. A demanding multimedia-based project in which students generated digital stories might give meaningful experience and increase improvement students’ spoken ability.